(untitled) (Iraqi Journal of Medical Sciences, 2019)
Tissue biopsy has been the mainstay in tumor diagnosis for centuries. But due to its invasiveness and the heterogeneity of tumors there was a need for an alternative or adjuvant techniques to diagnose and assess tumors. Liquid biopsy is emerging as a new technique that will open the way for the diagnosis, tumor characterization, assess disease prognosis and individualize treatment options in cancer patients. Keywords:Biopsy, CTC, ctDNA Citation: Mahdi AK. Liquid biopsy - A new prospect. Iraqi JMS. 2018; 16(4): 353-356. doi: 10.22578/IJMS.16.4.1